Synthesis, Characterization, and Evaluation of Boron-Doped Iron Oxides for the Photocatalytic Degradation of Atrazine under Visible Light - Shan Hu; Guanglong Liu; Duanwei Zhu; Chao Chen; Shuijiao Liao (International Journal of Photoenergy)
Photocatalytic degradation of atrazine by boron-doped iron oxides under visible light irradiation was investigated. In this work, boron-doped goethite and hematite were successfully prepared by sol-gel method with trimethylborate as boron precursor. The powders were characterized by XRD, UV-vis diffuse reflectance spectra, and porosimetry analysis. The results showed that boron doping could influence the crystal structure, enlarge the BET surface area, improve light absorption ability, and narrow their band-gap energy. The photocatalytic activity of B-doped iron oxides was evaluated in the degradation of atrazine under the visible light irradiation, and B-doped iron oxides showed higher atrazine degradation rate than that of pristine iron oxides. Particularly, B-doped goethite exhibited better photocatalytic activity than B-doped hematite.